2009
DOI: 10.1177/1523422309343680
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Scholar-Practitioner Binaries: Exploring the Liminal Possibilities of the Borderlands

Abstract: The recent discourse connected to the notion of scholar-practitioner in human resource development commonly uses the metaphor of a "gap" between these two binaries that must somehow be bridged or that otherwise requires linking. This article examines the contemporary expression of this gap in the AHRD literature and the nature of the duality it implies. An alternative metaphor based on Anzaldúa's borderlands and the mestiza consciousness that emerges there is suggested. This reframing and its implications are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
0
21
0
3
Order By: Relevance
“…(It is important to note that the premise of this article is not that all HRD scholarship should be communityengaged, but rather that CES deserves full consideration and recognition as a viable andvalued area of scholarship and practice for HRD scholar-practitioners.) Embedded within this discussion is the invitation for HRD scholar-practitioners to reflect on how espoused values of humanistic development (Bierema & Callahan, 2014) and democratic engagement (Hatcher, 2004) are enacted, alongside working to dissolve the boundaries-real or perceived-between research, theory, and practice at individual and collective levels (Saunders, 2011;Tsui, 2013b;Tyler, 2009). Boyer (1990) conceptualizes "scholarship" as having:…”
Section: Integrating Ces and Hrdmentioning
confidence: 99%
“…(It is important to note that the premise of this article is not that all HRD scholarship should be communityengaged, but rather that CES deserves full consideration and recognition as a viable andvalued area of scholarship and practice for HRD scholar-practitioners.) Embedded within this discussion is the invitation for HRD scholar-practitioners to reflect on how espoused values of humanistic development (Bierema & Callahan, 2014) and democratic engagement (Hatcher, 2004) are enacted, alongside working to dissolve the boundaries-real or perceived-between research, theory, and practice at individual and collective levels (Saunders, 2011;Tsui, 2013b;Tyler, 2009). Boyer (1990) conceptualizes "scholarship" as having:…”
Section: Integrating Ces and Hrdmentioning
confidence: 99%
“…Fronteiras são territórios que se estendem em todas as direções a partir de sua borda ou seu limite. Fronteira é a borda pela qual dois elementos se tocam e ao mesmo tempo se separam, borrando os limites de forma que não exista mais este ou aquele lado (TYLER, 2009). Por exemplo, a cor marrom clara da pele do mulato torna obscura e dúbia a pele como significante racial, fazendo com que o mulato não seja nem negro nem branco.…”
Section: Pós-colonialismo: Fronteiras Hibridade E Inteligibilidadeunclassified
“…O mulato é uma negociação discursiva de posição de identidade que sinaliza que ele não é exatamente negro, mas ocupa um espaço in-between (BHABHA, 1994(BHABHA, , 1996TATE, 2005). Tyler (2009) destaca que apesar de o binário facilitar o estabelecimento de fronteiras, a fronteira por si só não pode ser descrita e nem seve ao binário, pois as fronteiras têm como principal característica dissolver e não dominar dualidades. Fronteiras são lugares onde o espaço entre dois indivíduos diminuem com a intimidade (ANZALDÚA, 1987), produzindo novas conexões e possibilitando constantes transformações e modificações de ambos os lados, conectando uns aos outros, ou seja, fronteiras são coalizões culturais capazes de produzirem novas histórias (ANZALDÚA, 1987), "Migrando pelos entre-lugares da diferença, mostra como esta é constituída na história e adquire forma a partir de articulações sempre locaissuas mestiçagens múltiplas revelam simultaneamente mecanismos de sujeição e ocasiões para o exercício da liberdade" (COSTA;ÀVILA, 2005, p. 694).…”
Section: Pós-colonialismo: Fronteiras Hibridade E Inteligibilidadeunclassified
See 1 more Smart Citation
“…There is also an important role for practitioners to provide feedback to scholars who are engaged in theory building and testing. Another useful metaphor was provided by Tyler (2009). She suggested that we view the dynamics between research and practice as intersecting borderlands rather than bridging a gap.…”
Section: Bridging or Closing The Gap?mentioning
confidence: 99%